Landslide Intensity and Potential Based on Geomorphology and Their Relationship to the Stadia Level of The Karanggayam River, Kebumen Regency, Central Java Province, Indonesia - Retongga, Nofrohu; Razi, Muhammad Haikal; Hayatuzzahra, Sayidatina; Dirgantara, Aghib; Samsun, Samsun; Haris, M (Journal of Applied Geospatial Information, 2024)
Landslides are disasters, with a high incidence in the Kebumen Regency area. The Kebumen Regency Regional Disaster Management Agency (BPBD) recorded that from 2011 to 2020, there were 1,335 disaster events, 477 events (35.7%) were landslides, and most landslides occurred in Karanggayam District with a total of 43 disaster events, which is the number one landslide incident in Kebumen Regency. Landslides also occurred at several points along the Karanggayam River. The research method consists of three stages: a literature study, surface geological mapping, and field data processing. The strength and potential of landslides are connected to geomorphological conditions, which include morphology, morphogenesis, and morphoassociation. This is shown by field research results, geomorphological data analysis, and Karanggayam River stage data. The mature river stage level in the study area affects the strength and possibility of landslides caused by lateral erosion on the outer bend slopes of the river. These slopes are steep, have thick soil, less resistant rock types, and few to moderate plants.